Derechos laborales de los PPL para su reincorporación con la sociedad. propuesta normativa - Plaza Toala, Nicole Renata (2022)
The purpose of this research work was to establish a labor policy that contributes to the improvement of the labor reinsertion process of Persons Deprived of Liberty (PPL) or adult persons in conflict with the law in the Penitentiary Complex "Centro de Privación de Libertad Guayas No. 1". 1" Penitentiary Complex, during the execution of the sentence and after its completion; in observance of the current situation of the Penitentiary System, whose process of treatment of inmates is inadequate for the compliance of what the Constitution of the Republic of Ecuador and the Organic Integral Penal Code dictate. Based on a design with a qualitative approach and inductive method, a field study was developed through interviews with five practicing professionals with experience in the selected area of research, obtaining that the state's lack of compliance with the penitentiary treatment, the limited labor supply in the market, and the discriminatory culture that exists in the country, results in a lower labor competitiveness with respect to the average applicant; in view of which, a regulatory reform of Art. 9 and Art. 11 of the Interministerial Agreement between the Ministry of Labor and the Ministry of Justice, Human Rights and Worship, which emphasizes the development of their knowledge and personal entrepreneurship through productive activities for the benefit of labor reinsertion.